2016
DOI: 10.3109/02656736.2015.1129440
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia treatment planning for cervical cancer patients based on electrical conductivity tissue properties acquiredin vivowith EPT at 3 T MRI

Abstract: Introduction The reliability of hyperthermia treatment planning (HTP) is strongly dependent on the accuracy of the electric properties of each tissue. The values currently used are mostly based on ex vivo measurements. In this study, in vivo conductivity of human muscle, bladder content and cervical tumours, acquired with magnetic resonance-based electric properties tomography (MR-EPT), are exploited to investigate the effect on HTP for cervical cancer patients. Methods Temperature-based optimisation of five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 65 publications
0
73
0
Order By: Relevance
“…al. [24] presented the in vivo conductivity of human muscle, bladder content and cervical tumours, acquired with magnetic resonance-based electric properties tomography (MR-EPT). The temperature-based optimisation was performed with patient models based on conductivity values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [24] presented the in vivo conductivity of human muscle, bladder content and cervical tumours, acquired with magnetic resonance-based electric properties tomography (MR-EPT). The temperature-based optimisation was performed with patient models based on conductivity values.…”
Section: Introductionmentioning
confidence: 99%
“…A correlation between erysipelas (a streptococcal skin infection) and tumour regression had been observed for over a century before William Coley in 1891 [1] first documented evidence of a relationship between infection and cancer regression in sarcoma patients. Ever-expanding research on the hyperthermic treatment of cancer has been sustained over the past four decades [1][2][3][4][5][6][7][8][9][10][11][12]. In some hyperthermia treatments, the patient's blood is warmed up by an external device before it is re-transfused to the target volume (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A major step forward was the use of more reliable input data. Recent research has shown that the dielectric properties, and in particular the electric conductivity, of urine differ noticeably from the values hitherto used in our treatment planning system; this was shown to have a significant impact on the specific absorption rate (SAR) and temperature distributions in the pelvic area [31].…”
Section: Introductionmentioning
confidence: 91%
“…Knowledge of electrical tissue properties is necessary to build patient‐specific electromagnetic (EM) models, which are fundamental for radiofrequency (RF) safety and treatment planning for therapeutic heating of malignant tissues using RF or microwave antennas . For example, patient‐specific electrical properties may be used as input for planning in locoregional hyperthermia treatment of patients with pelvic tumors (e.g., cervix) with phased arrays of 70‐130 MHz antennas .…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of electrical tissue properties is necessary to build patient‐specific electromagnetic (EM) models, which are fundamental for radiofrequency (RF) safety and treatment planning for therapeutic heating of malignant tissues using RF or microwave antennas . For example, patient‐specific electrical properties may be used as input for planning in locoregional hyperthermia treatment of patients with pelvic tumors (e.g., cervix) with phased arrays of 70‐130 MHz antennas . In this frequency range, however, electrical properties might vary (e.g., the permittivity variation is 11% in muscle and 15% in the cervix) because of their dispersive nature; thus, electrical properties should be characterized at a frequency near the frequency used for treatment in order to improve the reliability of treatment planning.…”
Section: Introductionmentioning
confidence: 99%